Massive Machine Type Communications Multiple Access Schemes - Wang, Fanggang; Ma, Guoyu (SpringerBriefs in Electrical and Computer Engineering,, 2019)
This SpringerBrief introduces the current research status on emerging multiple access schemes for mMTC, which provides an integrated reference for future research works. A brief introduction on mMTC scenario is provided, and then the suitable random access procedure is discussed. Various multiple access schemes for mMTC are also described and analyzed in detail. It assumes a background in communication theory and wireless communication fundamentals. With the thriving of Internet of Things (IoT) industry, an emerging scenario named massive machine-type communication (mMTC) is considered in the future 5G networks. One main challenge in mMTC is how to support massive connections with limited radio resources and low energy consumption. Therein, novel multiple access scheme is the key to overcome the challenge. This SpringerBrief targets researchers and engineers, who are engaged in 5G and future IoT related communications system. It can also be a used as a reference book or a secondary text for graduate students, who major in communications.